Spatial variation of soil phosphorus in the water level fluctuation zone of the Three Gorges Reservoir: Coupling effects of elevation and artificial restoration - Qin, Dongming; Li, Shanze; Wang, Jingfu; Wang, Dengjun; Liao, Peng; Wang, Yuchun; Zhu, Zhiqiang; Dai, Zhihui; Jin, Zuxue; Hu, Xinping; Qiu, Shuoru; Ma, Yiming; et al. (The Science of the total environment, 2023)
The water level fluctuation zone (WLFZ) is a distinctive and important component of the reservoir ecosystem. Due to periodic inundation, the fraction, spatial distribution, and chemical reactivity of soil phosphorus (P) within the WLFZ can potentially impact the loading of P into reservoir waters. However, a detailed study of this subject is lacking. In this study, the soil P in the WLFZ of the Three Gorges Reservoir, China, was examined using a combination of chemical sequential extraction, 31P NMR, and adsorption experiments. The results of chemical sequential extraction showed that HCl-Pi constituted the largest P pool among all P forms, with a mean concentration of 338 mg/kg. The content of HCl-Pi decreased significantly toward the dam, while the content of Res-P decreased in the opposite direction. The highest contents of most P forms and total P were observed at an elevation of 160 m. 31P NMR measurements showed that NaOH-EDTA Pi detectable in WLFZ soils at 145 m, 160 m, and 175 m elevation consisted mainly of orthophosphate and pyrophosphate, while NaOH-EDTA Po contained phosphate monoesters and phosphate diesters, accounting for 1.4 % to 46.2 % of NaOH-EDTA TP. Adsorption experiments showed that soil P in the WLFZ was a potential P source for reservoir waters, with chemisorption being the dominant mechanism of P sequestration. The adsorption equilibrium concentration of WLFZ soil was lower at higher elevations (>170 m) compared to lower elevations (<150 m), exhibiting a decrease in the average maximum adsorption from 271 mg/kg to 192 mg/kg. Statistical analysis suggested that Ca and Fe content, particle size, elevation, and artificial restoration were key factors affecting the fraction and content of soil P in the WLFZ. Our findings contribute to an improved understanding of the behavior of soil P in the WLFZ of large reservoirs and its potential contribution to the reservoir waters. [Display omitted] •86 soils from 13 locations and 7 elevations were collected from the water level fluctuation zone.•HCl-Pi was the largest P pool among all P forms, with mean concentration of 338.5 mg/kg.•Phosphate monoester and phosphate diester accounted for 1.4 % to 46.2 % of NaOH-EDTA TP.•The sorption equilibrium concentration of WLFZ soil decreased with increasing elevation.•Ca and Fe content, particle size, and elevation were key factors affecting soil P fraction.